2021
DOI: 10.1021/acs.molpharmaceut.1c00085
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Hypoxia with PLGA-Encapsulated Manganese Dioxide Nanoparticles Improves Natural Killer Cell Response to Tumor Spheroids

Abstract: The adoptive transfer of natural killer (NK) cells, which can recognize and obliterate cancer cells, provides a practical alternative to current treatment modalities to improve cancer patients’ survival. However, translating NK cell therapies to treat solid tumors has proven challenging due to the tumor microenvironment (TME). Hypoxia in the TME induces immunosuppression that inhibits the cytotoxic function of NK cells. Thus, reversing hypoxia-induced immunosuppression is critical for effective adoptive NK cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 64 publications
3
29
0
1
Order By: Relevance
“…Recently, metal oxides have been demonstrated to have potential as oxygen-generating materials. Tetravalent manganese [Mn(IV)], which exists in the form of MnO 2 , can be used in nanoparticles as a convenient and straightforward way to construct a nanosystem with GSH-depletion ability 27 , 29 , 40 to overcome hypoxia and improve PDT/SDT efficiency. Hence, the role of MnO 2 in PHD@MnO 2 nanosystems was further explored in subsequent cellular and in vivo therapeutic effect experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, metal oxides have been demonstrated to have potential as oxygen-generating materials. Tetravalent manganese [Mn(IV)], which exists in the form of MnO 2 , can be used in nanoparticles as a convenient and straightforward way to construct a nanosystem with GSH-depletion ability 27 , 29 , 40 to overcome hypoxia and improve PDT/SDT efficiency. Hence, the role of MnO 2 in PHD@MnO 2 nanosystems was further explored in subsequent cellular and in vivo therapeutic effect experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of PLGA-MnO 2 /STM NPs (MSP): MnO 2 NPs were synthesized by reducing potassium permanganate with polyallylamine hydrochloride (PAH). [57] Briefly, KMnO4 (30 mg mL −1 ) was mixed with PAH (30 mg mL −1 ). After reacting for 30 min, MnO 2 NPs were obtained after purification.…”
Section: Methodsmentioning
confidence: 99%
“…Since LDH released from damaging cells, the amount of LDH release correlated to drug efficacy of preussin. In addition, Murphy et al, (2021) suggested a drug delivery model incorporating with manganese dioxide nanoparticles (MnO 2 NPs) to design controlled oxygen production and promote nature killer cell function [120]. To increase biocompatibility, MnO2 nanoparticles were encapsulated to poly(lactic-co-glytic), forming PLGA-MnO 2 NPs.…”
Section: Cell Viability Assaymentioning
confidence: 99%